Optimization of Genotyping-by-Sequencing (GBS) forGermplasm Fingerprinting and Trait Mapping in Faba Bean - Zhang, Hailin; Fechete, Lavinia; Himmelbach, Axel; Poehlein, Anja; Lohwasser, Ulrike; Börner, Andreas; Maalouf, Fouad; Agrawal, Shiv Kumar; Khazaei, Hamid; Stein, Nils; Jayakodi, Murukarthick (Wiley Open Access, 2024)
Faba bean (Vicia faba L.) is an important pulse crop with a wide range of agroecological adaptations. The development of genomic tools and a comprehensive catalog of extant genetic diversity are crucial for developing improved faba bean cultivars. The lack of a cost-effective genotyping platform limits the characterization of large germplasm collections, understanding of genetic diversity across populations, and implementing breeder's tools like genomic selection. Genotyping-by-sequencing (GBS) offers high-resolution genotyping for both model and crop plant species, even without a reference genome sequence. The genome fragments targeted by GBS depend substantially on the restriction enzyme (RE) used for the complexity reduction step. Species with complex genomic architecture require optimization of GBS with proper RE to realize the full potential of GBS. Here, we evaluated various REs in the GBS method and identified that the combination of ApeKI/MseI proved to be the most appropriate for faba bean based on the best library quality, a high number of genomic loci spread across chromosomes, and high enrichment loci associated with the gene space. With the new optimized protocol, we constructed a genetic map using a recombinant inbred line (RIL) population and identified a QTL for seed hilum color on Chromosome 1. In addition, we also genotyped a diversity panel and performed a genome-wide association studies (GWAS) for important agronomic traits, including plant height (PH), flowering time (FT), and number of pods per plant (PPP). We identified six SNP markers significantly associated with these traits and listed potential candidate genes. The optimized faba bean-specific GBS procedure will facilitate access to the untapped genetic diversity for genetic research and breeding and may facilitate functional genomics.